Increasing the Carbon Flux toward Synthesis of Short-Chain-Length-Medium-Chain-Length Polyhydroxyalkanoate in the Peroxisome of Saccharomyces cerevisiae through Modification of the β-Oxidation Cycle - de Oliveira, Valeria Cora (American Society for Microbiology, 2004)
Short-chain-length-medium-chain-length polyhydroxyalkanoates were synthesized in Saccharomyces cerevisiae from intermediates of the β-oxidation cycle by expressing the polyhydroxyalkanoate synthases from Aeromonas caviae and Ralstonia eutropha in the peroxisomes. The quantity of polymer produced was increased by using a mutant of the β-oxidation-associated multifunctional enzyme with low dehydrogenase activity toward R-3-hydroxybutyryl coenzyme A.